Análisis Financiero a la Cooperativa de Ahorro y Crédito Educadores de Loja-CACEL Ltda. de la Ciudad de Loja, periodos 2021-2022 - Romero Bravo, Maritza del Cisne (2024)
The present work called "Financial Analysis of the Cooperativa de Ahorro y Crédito Educadores de Loja-CACEL Ltda. of the City of Loja, periods 2021-2022'' was developed in order to comply with the general and specific objectives, and thus analyze the financial and economic situation of the Cooperative. We proceeded to collect the necessary documentation in order to prepare the vertical analysis of the information presented in the financial statements in which the financial structure and the participation of the percentages equivalent to each account involved in the economic-financial position of the cooperative are established, with their respective graphical representation and interpretation, in addition the horizontal analysis was performed in which the financial movements and variations are established, being these increases or decreases of the figures in the financial statements included in the period of study 2021-2022. For the development of the second specific objective, the financial indicators required by the Superintendencia de Economía Popular y Solidaria were used to evaluate the economic and financial situation of the cooperative. These findings allowed concluding that the cooperative experienced a beneficial decrease in its delinquency levels, which is related to the increase in the value of the loan portfolio. Finally, the development of the third specific objective was carried out through the preparation of a financial report. In this report, the results of the analysis were presented in a clear and understandable manner. In addition, conclusions and recommendations were included with the purpose of making known the most important points that will help for the correct decision making of the administrators allowing to maintain the cooperative in a good financial position.